Bonding material and bonded structure

By using single particles and composite particles in the bonding material and promoting the formation of intermetallic compounds through flux, the problems of high temperature and long heating time of the bonding part when SiC and GaN elements are used are solved, and the high strength of the bonding part is achieved and heat resistance.

CN119421760APending Publication Date: 2025-02-11PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380049152.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-05
Filing Date
2023-06-15
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

When using SiC elements and GaN elements, the temperature Tj of the joint portion reaches 200 to 250°C. The existing solder materials are difficult to meet the requirements of heat resistance, and the liquid phase diffusion takes a long time, so there is a problem of excessive heating time.

Method used

Using a bonding material containing a single particle and a composite particle, the single particle is the first metal with a low melting point metal, and the composite particle is the first metal central core with a high melting point metal fine particle coating layer, and the intermetallic compound is promoted through the reducing agent component of the flux. The formation of the bonding time is shortened.

Benefits of technology

The high strength and heat resistance of the joint part are achieved, the bonding time is shortened, the thermal damage to the surrounding components is reduced, and the efficiency and reliability of the joint material is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119421760A_ABST
    Figure CN119421760A_ABST
Patent Text Reader

Abstract

The bonding material includes: single particles that are particles of a first metal; composite particles provided with a central core which is a particle of a first metal, and at least one coating layer which covers the entire surface of the central core and which is composed of fine particles of a second metal; and a flux having a reducing agent component, the first metal and the second metal being capable of forming an intermetallic compound, and the reducing agent component of the flux being present between the central core and the coating layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a joined structure having a structure in which two members are joined by a joining material containing a metal material and is used in devices such as power devices, and a joining material used for producing the joined structure. Background Art

[0002] In the case of equipment such as power devices that have semiconductor elements that generate heat, in order to dissipate the heat generated by the semiconductor elements, there is sometimes a joining structure formed by joining two components, namely a substrate and a heat dissipation portion, in order to transfer heat from a substrate on which the semiconductor elements are mounted to a heat dissipation portion.

[0003] In recent years, from the perspective of energy saving, the use of next-generation power device elements such as SiC elements and GaN elements, which have the advantage of being able to control power with high efficiency, has increased as power devices, starting from the previous Si elements. These next-generation power device elements have the advantage of being able to operate even at high temperatures, and can withstand greater heat generation than previous Si elements, so sometimes larger currents are controlled to flow. However, if a larger current flows, the heat generated from the semiconductor element increases, and the semiconductor element is exposed to a higher temperature. As a result, the temperature T of the joint between the electrode such as the lead frame for flowing the current controlled by the semiconductor element and the element electrode increases. j For example, the temperature T of the joint is j When using conventional Si devices, the temperature is about 125°C, but when using SiC devices and GaN devices, the temperature reaches 200 to 250°C.

[0004] Therefore, the junction between the element electrode and the lead frame electrode requires a high thermal conductivity for efficiently releasing the generated heat to the lead frame and a high temperature T of the junction that can also be increased. j Heat resistance.

[0005] Conventionally, solder materials have been widely used as bonding materials for bonding a bonding structure that uses a conductor to bond a device electrode to a lead frame electrode, since bonding can be performed at low temperatures. However, the bonding temperature T j That is, 200 to 250°C is a temperature near or above the melting point of commonly used solder materials containing Sn and Pb as main components, which is a very severe temperature. Therefore, in a joint structure using these solder materials as joints, it is difficult to ensure heat resistance when using SiC devices and GaN devices.

[0006] To address this issue, a transient-liquid-phase (TLP) bonding method was proposed. TLP bonding is performed by bringing a high melting point metal into contact with a low melting point metal, melting the low melting point metal, and forming an intermetallic compound with the high melting point metal through their mutual diffusion. As a result, the remelting temperature of the joint becomes higher due to the joining temperature, and the maximum operating temperature can be made higher than the joining temperature. However, since mutual diffusion takes a long time, there is a problem of requiring a long heating time.

[0007] In view of such a problem, a method for shortening the time of mutual diffusion by using high melting point metal as nanoparticles has been proposed. However, nanoparticles have a large surface energy, and when mixed with low melting point metals as a bonding material, they adhere to the surface of the low melting point metal and completely encapsulate or cover the surface, so there is a problem that the solubility of the low melting point metal deteriorates and the strength of the bonding portion weakens.

[0008] As a bonding material for solving such a problem, the following technology is disclosed for ensuring meltability by using metal particles, wherein fine particles of any of Ag, Cu, Bi or Ge, which are high-melting-point metals, are precipitated in the form of islands and attached to the surface of Sn, which is a low-melting-point metal, or an alloy of Sn and Cu, which has an average particle size of 5 μm (for example, refer to Patent Document 1).

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2011-177719 Summary of the invention

[0012] A bonding material in one embodiment of the present invention includes: a single particle which is a particle of a first metal; a composite particle which has a central core which is a particle of the first metal, and at least one coating layer which covers the entire surface of the central core and is composed of particles of a second metal; and a flux which has a reducing agent component, wherein the first metal and the second metal can form an intermetallic compound, and the reducing agent component of the flux exists between the central core and the coating layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a diagram showing an example of metal particles according to the first embodiment.

[0014] Figure 2 This is a cross-sectional SEM image of the bonding material after heating according to the example of the present embodiment.

[0015] Figure 3 This is a cross-sectional SEM image of the bonding material of the comparative example of the present embodiment after heating.

[0016] Figure 4 This is a table showing the ratio of the mass of the first metal particles and the second metal particles to the total mass of the metal contained in the bonding material paste in Example 1 and Comparative Example 1, and the results of the above evaluation.

[0017] Figure 5 This is a table showing the ratio of the mass of the first metal particles and the second metal particles to the total mass of the metal contained in the bonding material paste in Example 2 and Comparative Example 2, and the results of the above evaluation.

[0018] Figure 6 This is a table showing the average particle diameters of the composite particles and single particles of the first metal particles in Example 3, and the results of the above-mentioned evaluations. DETAILED DESCRIPTION

[0019] (Process of Completion of the Invention)

[0020] In the bonding material for bonding the element electrode to the metal member by TLP bonding of the metal, if the content of the high melting point metal of the particles attached in the form of islands increases, the surface of the low melting point metal will be encapsulated or coated. Therefore, it is necessary to reduce the content of the particles. In this case, the entire amount of the low melting point metal cannot form an intermetallic compound, and the low melting point metal remains in the bonding portion, which makes it difficult to ensure the heat resistance of the bonding portion.

[0021] As a bonding material for bonding an element electrode to a metal component by TLP bonding of metal, the inventors have studied bonding materials containing a low melting point metal in two forms, single particles and composite particles. The single particle is a particle of a first metal of a low melting point metal. The composite particle has a central core as the first metal particle, and at least one layer of a coating layer consisting of microparticles of a second metal of a high melting point metal covering the entire surface of the central core. The bonding material contains a certain amount of high melting point metal content of microparticles, and the low melting point metal is fully contained by the single particles and the composite particles. The inventors have studied a bonding structure formed by bonding an element electrode to a metal component using a bonding material containing the composite particles and the single particles.

[0022] The above-mentioned bonding material contains particles of the second metal as a high melting point metal, so that the time required for bonding can be shortened and thermal damage to surrounding components during bonding can be suppressed. On the other hand, the first metal as a low melting point metal exists in the form of a single particle and a central core of a composite particle. In particular, the particles of the second metal covering the central core of the composite particle react with the first metal to form an intermetallic compound. In addition, the single particle becomes a liquid phase by heating, becomes the parent phase of the composite particle, and contributes to the generation of the intermetallic compound. Thus, a high melting point intermetallic compound can be obtained, and heat resistance can be obtained.

[0023] The bonding material layer formed by the above bonding material is heated to a temperature above the temperature at which the liquid phase containing the first metal is partially generated (hereinafter referred to as the "liquid phase generation temperature") to form a liquid phase containing the first metal, and the first metal in the composite particles reacts with the second metal to generate an intermetallic compound. At this time, a bonding layer is formed in which the composite particles are connected to each other by the intermetallic compound generated by the reaction of the first metal contained in the single particle with the second metal on the surface of the composite particle. As a result, it was found that the element electrode can be bonded to the metal component using a bonding layer with high bonding strength and heat resistance, thereby completing the present invention.

[0024] The present invention is to solve the conventional problems, and an object of the present invention is to provide a joining material having excellent strength and heat resistance of a joining portion.

[0025] The first type of bonding material includes: a single particle which is a particle of a first metal; a composite particle which has a central core which is a particle of the first metal, and at least one coating layer which covers the entire surface of the central core and is composed of particles of a second metal; and a flux which has a reducing agent component, wherein the first metal and the second metal can form an intermetallic compound, and the reducing agent component of the flux exists between the central core and the coating layer.

[0026] Regarding the bonding material of the second aspect, in the above-mentioned first aspect, the first metal may be a Sn alloy.

[0027] Regarding the bonding material of the third aspect, in the first or second aspect described above, the second metal may be Cu.

[0028] Regarding the bonding material of a fourth aspect, in the first or third aspect, the first metal may be a Sn—Bi alloy.

[0029] Regarding the bonding material of the fifth aspect, in the fourth aspect, the content of Bi in the Sn—Bi alloy may be such that the liquidus temperature is 150° C. or less in the equilibrium phase diagram of the Sn—Bi alloy.

[0030] Regarding the bonding material of the sixth aspect, in the fourth aspect, the content of Bi in the Sn—Bi alloy may be 52 to 62% by mass.

[0031] Regarding the bonding material of a seventh aspect, in any one of the first to sixth aspects, when the total mass of the single particles and the composite particles is 100 mass %, the fine particles of the second metal may be 30 to 40 mass %.

[0032] Regarding the bonding material of an eighth aspect, in any one of the first to seventh aspects, the average particle diameter of the first metal particles serving as the central core of the composite particles may be 2 to 10 μm.

[0033] Regarding the bonding material of a ninth aspect, in any one of the first to eighth aspects, the average particle size of the first metal particles as single particles may be 2 to 38 μm.

[0034] Regarding the bonding material of a tenth aspect, in any one of the first to ninth aspects, the average particle size of the second metal fine particles may be 50 to 500 nm.

[0035] Regarding the bonding material of an eleventh aspect, in any one of the first to tenth aspects, the reducing agent component may be an alkanolamine.

[0036] A joined structure according to a twelfth aspect includes an element electrode, a metal member, and the joining material according to any one of the first to eleventh aspects for joining the element electrode and the metal member.

[0037] As described above, according to the bonding material of the present invention, the time required for bonding is shortened, thereby reducing thermal damage to surrounding members during bonding, and can prevent deterioration in meltability during heating due to the use of the above-mentioned fine particles, thereby providing a bonding material with excellent strength and heat resistance of the bonding portion.

[0038] Hereinafter, a joining material and a joined structure according to an embodiment of the present invention will be described in detail with reference to the drawings.

[0039] (Implementation method 1)

[0040] <Joining materials>

[0041] The bonding material of the first embodiment of the present invention comprises a single particle, a composite particle and a soldering flux. The single particle is a particle of the first metal. The composite particle has a central core as a particle of the first metal, and at least one layer of a coating layer consisting of particles of the second metal covering the entire surface of the central core. The soldering flux has a reducing agent component. The first metal and the second metal can form an intermetallic compound. In addition, the reducing agent component of the soldering flux exists between the central core and the coating layer. By using composite particles and single particles, there is a tendency to improve the strength and heat resistance of the bonding portion.

[0042] Hereinafter, constituent members used in the bonding material will be described below.

[0043] <Single particle (first metal particle)>

[0044] The single particle (first metal particle) used in the present invention contains Sn, for example. Since the first metal has a low liquid phase generation temperature, a liquid phase is formed by the first metal particle before the second metal particle is sintered, and a strong bonding interface is formed by wetting and chemical reaction with the bonded member. In addition, by causing liquid phase diffusion between the liquid phase and the second metal particle, an intermetallic compound can be formed to form a bonding layer with excellent heat resistance. The bonding portion is formed by heating above the liquid phase generation temperature of the first metal particle. In addition, the heating temperature is preferably the same as that of the conventional solder. Therefore, as the liquid phase generation temperature, it is preferably below 150°C (liquid phase generation temperature ≤ 150°C).

[0045] As such an alloy, a Sn-Bi alloy is preferred. The composition of such an alloy is not particularly limited as long as the liquid phase formation temperature (liquidus temperature) is 150° C. or less, but a composition with a lower liquid phase formation temperature (liquidus temperature) is preferred, and a eutectic composition is particularly preferred.

[0046] In particular, when the first metal is a Sn-Bi alloy, it is preferred that a liquid phase is easily formed from the first metal, and a bonding layer having excellent bonding strength can be reliably formed. The atomic ratio of Sn to Bi in the Sn-Bi alloy is preferably an atomic ratio that becomes a liquid phase at 150° C., as determined from the equilibrium phase diagram of the Sn-Bi alloy. Specifically, the atomic ratio of Bi in the Sn-Bi alloy is preferably 52 to 62% by mass.

[0047] The average particle size of the first metal particle as a single particle is preferably 2 to 38 μm. If the average particle size of the first metal of a single particle exceeds the upper limit (38 μm), it will be greatly different from the particle size of the composite particles, and uniform kneading cannot be performed, and there is a tendency for the coated particles to agglomerate and reduce the bonding strength. In addition, if the average particle size of the first metal of a single particle is lower than the lower limit (2 μm), the total surface area of ​​the first metal particle increases, so the oxide film of the first metal particle increases, and there is a tendency for the first metal particle to have poor solubility and reduced bonding strength.

[0048] The average particle size is calculated using a laser particle size distribution analyzer. The average particle size is the value of the median particle size d50% (μm, volume conversion). The same applies to the following.

[0049] <Composite particles>

[0050] The average particle size of the first metal particle serving as the central core of the composite particle is preferably 2 to 10 μm. If the average particle size of the first metal of the composite particle exceeds the upper limit (10 μm), the total surface area of ​​the first metal particle serving as the central core of the composite particle becomes smaller, the number of second metal particles that can be attached to the surface of the first metal particle decreases, and there are remaining second metal particles. The remaining second metal particles cover the surface of the single particle, causing the bonding strength to decrease, and the remaining second metal particles agglomerate in the bonding layer, causing the reliability of the bonding portion to decrease. In addition, if the average particle size of the first metal particle serving as the central core of the composite particle is lower than the lower limit (2 μm), the total surface area of ​​the first metal particle increases, so the oxide film of the first metal particle increases, and there is a tendency for the first metal particle to have poor solubility and reduced bonding strength.

[0051] When the total mass of the single particle and the first metal particle as the central core of the composite particle is set to 100 mass%, the ratio of the single particle is preferably 30 to 60 mass%. If the ratio of the single particle exceeds 60 mass%, the second metal particles constituting the composite particle become excessive, and the second metal particles agglomerate with each other in the bonding layer, and there is a tendency for the reliability of the bonding portion to decrease. In addition, if the ratio of the single particle is less than 30 mass%, the composite particles cannot be connected to each other, so there is a tendency for the strength of the bonding portion to decrease.

[0052] <Second Metal Particle>

[0053] The second metal is preferably a metal having a higher melting point than the first metal and capable of forming an intermetallic compound with the first metal contained in the first metal, and Cu is particularly preferred. The average particle size of the second metal particles is preferably 50 to 500 nm. If the average particle size of the second metal particles exceeds the upper limit (500 nm), the contact area with the first metal particles becomes smaller, and there is a tendency that the time required for bonding becomes longer. In addition, the average particle size of the second metal particles is preferably 50 nm or more from the viewpoint of maintaining the characteristics as a metal.

[0054] When the total mass of the single particles and the composite particles is set to 100 mass %, the ratio of the particles of the second metal is preferably 30 to 40 mass %. If the content of the second metal particles is less than the lower limit (30 mass %), the formation of the intermetallic compound caused by the liquid phase diffusion reaction between the molten first metal and the second metal particles becomes insufficient, and the first metal that cannot form the intermetallic compound remains in the bonding layer, and there is a tendency for the heat resistance of the bonding layer to decrease. In addition, if the content of the second metal particles exceeds the upper limit (40 mass %), the second metal particles that cannot form the intermetallic compound remain in the bonding layer too much, and there is a tendency for the strength of the bonding layer to decrease.

[0055] <Flux>

[0056] As the reducing agent component of the flux between the central core and the coating layer in the composite particle, alkanolamines are preferred. The alkanolamines coat the surface of the first metal particle as the central core of the composite particle, and the second metal fine particles adhere to the coating layer, thereby forming a strong bond.

[0057] <Method for producing a bonded structure>

[0058] The method for manufacturing the bonded structure according to the first embodiment includes the following three steps.

[0059] (1) a step of forming a laminated body comprising a first member, a second member, and a bonding material layer formed using the bonding material of the present invention and in contact with surfaces of the first member and the second member using the bonding material described above;

[0060] (2) a step of heating the bonding material layer at a temperature not lower than a liquid phase generation temperature to form a liquid phase containing a first metal;

[0061] (3) A step of causing the first metal and the second metal to react to form an intermetallic compound to form a bonding layer, and bonding the first member and the second member using the bonding layer.

[0062] (1) In the bonding method of the present invention, first, a laminate is formed, the laminate comprising a first member, a second member, and a bonding material layer formed using the bonding material of the present invention and in contact with the surfaces of the first member and the second member. There is no particular limitation on the method for forming such a laminate, and for example, a method of printing or applying the bonding material of embodiment 1 of the present invention on the surface of the first member and arranging the second member on the surface of the formed bonding material layer can be cited.

[0063] As the first member, there is no particular limitation as long as the surface is metal, and examples thereof include Cu plates (e.g., semiconductor substrates), ceramic plates with metal attached to the surface, and alloy plates such as Cu alloys and Ni alloys. In addition, as the second member, there is no particular limitation as long as the surface is metal, and examples thereof include semiconductor elements (Si chips, SIC chips, GaN chips), and metal plates (Cu plates, Ni plates, and Al plates).

[0064] In addition, it is preferred that at least one of the areas in contact with the bonding material layer on the surface of the first component and the areas in contact with the bonding material layer on the surface of the second component contains a metal that can generate an intermetallic compound (preferably an intermetallic compound with a melting point of 250°C or more) by reacting with at least one of the first metal and the second metal. As a result, the bonding strength between the first component, the second component and the bonding layer is improved. In addition, in the case of containing a metal that can generate an intermetallic compound with a melting point of 250°C or more, there is a tendency that the heat resistance of the bonding layer is also improved. As such a metal that can generate an intermetallic compound by reacting with at least one of the first metal and the second metal, for example, Au, Ag, Cu, and Ni can be cited. Such a metal can be used alone, or two or more can be used in combination. In addition, when two or more metals are used, an alloy can also be formed.

[0065] (2) and (3) Next, the stacked body consisting of the first component / joining material layer / second component thus formed is heated at a predetermined temperature to form a liquid phase containing the first metal, so that the first metal and the second metal react to generate an intermetallic compound, thereby forming a joining layer with excellent joining strength (more preferably a joining layer with excellent electrical conductivity and thermal conductivity).

[0066] That is, first, the bonding material layer is heated above the liquid phase generation temperature. Thus, before the second metal is sintered, a liquid phase is formed by the first metal. The composite particles react with the second metal attached to the surface to generate an intermetallic compound. In addition, the single particles wet and spread between the composite particles that have generated the intermetallic compound like a binder, and react with the second metal particles of the outermost shell of the composite particles to generate the intermetallic compound. Thus, the generation of the intermetallic compound occurs uniformly in the bonding layer, forming a bonding layer with excellent bonding strength (more preferably a bonding layer with excellent electrical conductivity and thermal conductivity).

[0067] In addition, when a component is used as at least one of the first component and the second component, in which a metal capable of forming an intermetallic compound by reacting with the first metal in the contact area with the bonding material layer on the surface, the metal contained in the contact area reacts with the first metal through the heat treatment to further generate an intermetallic compound, thereby forming a bonding layer with further improved bonding strength.

[0068] For example, when a semiconductor substrate is used as the first component and a semiconductor element is used as the second component, a semiconductor device having excellent bonding strength between the semiconductor element and the semiconductor substrate can be manufactured by the bonding method of the present invention, wherein the semiconductor device comprises a semiconductor element, a semiconductor substrate, and a bonding layer disposed between the semiconductor element and the semiconductor substrate and formed using a bonding material. In particular, when a semiconductor element and a semiconductor substrate are used as at least one of the semiconductor element and the semiconductor substrate (preferably both), a metal that can react with the first metal to form an intermetallic compound in the contact region with the bonding layer on the surface, a semiconductor device having further improved bonding strength between the semiconductor element and the semiconductor substrate can be manufactured. In addition, when a semiconductor element and a semiconductor substrate are used as at least one of the semiconductor element and the semiconductor substrate (preferably both), a metal that can react with the first metal to form an intermetallic compound with a melting point of 250° C. or more in the contact region with the bonding layer on the surface, a semiconductor device having better heat resistance can be manufactured.

[0069] Example

[0070] The present invention will be described in detail based on Examples, but the present invention is not limited to these Examples.

[0071] [Example 1]

[0072] 1. Fabrication of the joint structure

[0073] As the first metal particles, SnBi particles having an average particle diameter of 2 to 6 μm were prepared, and as the second metal particles, Cu nanoparticles having an average particle diameter of 200 nm were prepared.

[0074] The bonding material is prepared by mixing the first metal particles and the second metal particles in such a manner that the total amount of the first metal particles and the second metal particles is 90% by mass of the total amount of the paste, the amount of triethanolamine as a reducing agent is 2.1% by mass, and the total amount of the organic solvent and the activator is 7.9% by mass. At this time, the first metal particles and the second metal particles are mixed in different ratios to obtain a plurality of bonding materials. In the total amount of the first metal particles and the second metal particles, in Example 1-1, the proportion of the first metal particles is set to 60% by mass, and the proportion of the second metal particles is set to 40% by mass. In Example 1-2, the proportion of the first metal particles is set to 65% by mass, and the proportion of the second metal particles is set to 35% by mass to prepare the bonding material.

[0075] In the method for manufacturing a bonding material, 50% by mass of the entire first metal particle is mixed with triethanolamine, the surface of the first metal particle is coated with a reducing agent, and then mixed with a second metal particle to obtain a composite particle. The obtained composite particle is kneaded with a single particle as the remainder of the first metal particle and a flux to obtain a bonding material paste.

[0076] For the bonded structure, oxygen-free Cu was used as the substrate, and Si chips (electrode plating Ti / Ni / Au) 1 mm were used as the components. The bonding material was applied on the substrate using a 100 μm thick metal mask, and the Si chip was stacked on the resulting bonding material layer.

[0077] The obtained laminate was heated at a firing temperature of 200° C. for 10 minutes in a nitrogen atmosphere at atmospheric pressure while the laminated surface was pressed at 1.36 N, thereby obtaining a bonded structure. The heating rate during the heating was set to 3° C. / s.

[0078] 2. Evaluation

[0079] (Joint strength)

[0080] The bonding strength between the substrate and the Si chip in the bonded structure obtained above was measured by the above method. In any bonded structure, the fracture site was within the bonding layer.

[0081] When the bonding strength was 20 MPa or more, it was evaluated that the bonding strength was high. If the bonding strength was high, it was expressed as "high", and if the bonding strength was low, it was expressed as "low".

[0082] (Remaining first metal particles)

[0083] The bonding strength was evaluated by measuring the heat resistance of the bonding portion at a substrate temperature of 200° C. In addition, an image was taken with a SEM at 3000 times magnification, and when phases with different brightness were confirmed in the SEM image, energy dispersive X-ray analysis (EDX analysis) of the phases with different brightness was performed.

[0084] In the EDX analysis, when the phase with different brightness is a phase composed of only the first metal, it is determined that the first metal particles remain without forming an intermetallic compound.

[0085] A bonding material having high bonding strength and no residual first metal particles was determined to be acceptable.

[0086] exist Figure 4 Table 1 shows the ratio of the mass of the first metal particles and the second metal particles in Example 1 and Comparative Example 1 to the total mass of the metal contained in the bonding material paste and the results of the above evaluation.

[0087] [Comparative Example 1]

[0088] In Comparative Example 1, the total amount of the first metal particles and the second metal particles was such that the ratio of the first metal particles was 50% and the ratio of the second metal particles was 50% by mass in Comparative Example 1-1, and the ratio of the first metal particles was 70% by mass and the ratio of the second metal particles was 30% by mass in Comparative Example 1-2 to prepare a bonding material. Regarding other conditions, a bonding structure was prepared and evaluated in the same manner as in Example 1.

[0089] according to Figure 4 As shown in Table 1, when the bonding material of the present invention is used (Examples 1-1 to 1-2), bonding can be performed with high bonding strength compared to when a bonding material exceeding the upper limit (40 mass %) of the ratio of the second metal particles is used (Comparative Example 1-1). In addition, when the bonding material of the present invention is used, compared to when a bonding material below the lower limit of the ratio of the second metal particles is used (Comparative Example 1-2), no first metal particles are observed to remain, and the bonding layer has excellent heat resistance.

[0090] [Example 2]

[0091] In Example 2, the first metal particles and the second metal particles were mixed so that the total amount of the paste was 92% by mass, the amount of triethanolamine as a reducing agent was 1.7% by mass, and the total amount of the organic solvent and the activator was 6.3% by mass to prepare the bonding material. Regarding other conditions, the bonding structure was prepared and evaluated in the same manner as in Example 1.

[0092] [Comparative Example 2]

[0093] As a method for producing a bonding material, the first metal particles were mixed with the second metal fine particles without coating the surface of the first metal particles with a reducing agent, thereby preparing a bonding material so that the ratio of the composite particles was 100%. Regarding other conditions, a bonding structure was produced and evaluated in the same manner as in Example 1.

[0094] exist Figure 5 Table 2 shows the ratio of the mass of the first metal particles and the second metal particles to the total mass of the metal contained in the bonding material paste and the results of the above evaluation in Example 2 and Comparative Example 2. It should be noted that the results of Example 1-1 and Example 1-2 are also shown for comparison.

[0095] exist Figure 2 The cross-sectional SEM image of the bonding material after heating of Example 2 is shown in FIG. Figure 3 : A cross-sectional SEM image of the bonding material of Comparative Example 2 after heating is shown.

[0096] exist Figure 2 In the structure after joining, no residual first metal phase was found. In the joined structure of Example 2, it was confirmed that the first metal and the second metal reacted to form an intermetallic compound well. Figure 2 The parent phase is composed of a CuSn alloy and a Bi phase formed by the reaction of the first metal and the second metal in the composite particles, and the second metal particles in the outermost shell of the single particles and the composite particles. The spherical Bi phase is the central core of the composite particles after the reaction. In other words, it is confirmed that the composite particles are connected to each other and the bonding strength is good. On the other hand, Figure 3 In the bonding structure of Comparative Example 2, the presence of the residual first metal phase was confirmed, and the formation of the intermetallic compound did not proceed so well. In addition, the shape of the second metal fine particles could be confirmed between the composite particles, and it was confirmed that the bonding strength was not so good.

[0097] according to Figure 5 As shown in Table 2, the case of using the bonding material of the present invention (Example 2) can be bonded with high bonding strength compared to the case of using a bonding material in which there is no reducing agent component of the flux between the center core and the coating layer in the composite particles (Comparative Example 2). In addition, no residue of the first metal particles was observed, so it can be seen that the strength and heat resistance of the bonding layer are excellent.

[0098] [Example 3]

[0099] In Example 3, a bonding material paste is prepared in such a manner that the average particle size of the composite particles and the average particle size of the single particles are different among the first metal particles. In Example 3-1, the average particle size of the first metal particles used in the composite particles is set to 10 μm, and the average particle size of the first metal particles used in the single particles is set to 2 to 6 μm. In Example 3-2, the average particle size of the first metal particles used in the composite particles is set to 2 to 6 μm, and the average particle size of the first metal particles used in the single particles is set to 10 μm. In Example 3-3, the average particle size of the first metal particles used in the composite particles is set to 2 to 6 μm, and the average particle size of the first metal particles used in the single particles is set to 20 to 38 μm. Regarding other conditions, a bonding structure is prepared and evaluated in the same manner as in Example 1.

[0100] [Comparative Example 3]

[0101] In Comparative Example 3, the average particle size of the first metal particles used in the composite particles was 2 to 6 μm, and the average particle size of the first metal particles used in the single particles was 45 to 75 μm. Regarding other conditions, a bonded structure was prepared and evaluated in the same manner as in Example 1.

[0102] exist Figure 6Table 3 shows the average particle diameters of the composite particles and single particles of the first metal particles in Example 3 and the results of the above evaluation.

[0103] according to Figure 6 As shown in Table 3, the case where the bonding material of the present invention was used (Examples 3-1 to 3-3) could achieve bonding with higher bonding strength than the case where a bonding material exceeding the upper limit (38 μm) of the average particle size of single particles of the present invention was used (Comparative Example 3).

[0104] Industrial Applicability

[0105] According to the bonding material of the present invention, the time required for bonding in devices with large heat generation such as power devices can be shortened, and the thermal damage to surrounding components during bonding can be reduced. In addition, the deterioration of the melting property during heating caused by the use of microparticles can be prevented, and a bonding material with excellent strength and heat resistance of the bonding portion can be provided.

[0106] Description of Reference Numerals

[0107] 101: Composite Particles

[0108] 102: Single Particle

Claims

1. A bonding material comprising: A single particle that is a particle of a first metal; A composite particle comprising a central core which is a particle of the first metal, and at least one coating layer which covers the entire surface of the central core and is composed of fine particles of a second metal; and A soldering flux having a reducing agent component, The first metal and the second metal are capable of forming an intermetallic compound, The reducing agent component of the soldering flux exists between the central core and the covering layer.

2. The bonding material according to claim 1, wherein The first metal is a Sn alloy.

3. The bonding material according to claim 1 or 2, wherein The second metal is Cu.

4. The bonding material according to claim 1, wherein The first metal is a Sn-Bi alloy.

5. The bonding material according to claim 4, wherein The Bi content in the Sn—Bi alloy is a content that makes the liquidus temperature 150° C. or less in the equilibrium phase diagram of the Sn—Bi alloy. The bonding material according to claim 4 , wherein: The content of Bi in the Sn—Bi alloy is 52 mass % to 62 mass %.

7. The bonding material according to claim 1, wherein When the total mass of the single particles and the composite particles is 100 mass %, the second metal fine particles account for 30 mass % to 40 mass %.

8. The bonding material according to claim 2, wherein The average particle size of the first metal particles serving as the central core of the composite particles is 2 μm to 10 μm.

9. The bonding material according to claim 2, wherein The average particle size of the first metal particles as the single particles is 2 μm to 38 μm.

10. The bonding material according to claim 1, wherein The average particle size of the second metal fine particles is 50 nm to 500 nm.

11. The bonding material according to claim 1, wherein The reducing agent component is alkanolamines. 12 . A joined structure comprising an element electrode, a metal member, and the joining material according to claim 1 for joining the element electrode and the metal member.

Citation Information

Patent Citations

  • Solder powder and paste for solder using the powder

    JP2011177719A